1988
DOI: 10.1136/adc.63.10.1207
|View full text |Cite
|
Sign up to set email alerts
|

Increased recall rate at screening for congenital hypothyroidism in breast fed infants born to iodine overloaded mothers.

Abstract: SUMMARY Skin disinfection with povidine-iodine (PVP-I) is widely used in obstetrics. We evaluated the influence of PVP-I in mothers at delivery on the serum thyroid stimulating hormone concentrations of their infants at the time of screening for congenital hypothyroidism. The study covered 4745 infants who were either breast fed (3659, 77%) or bottle fed (1086, 23%); 3086 (65%) of them were born to mothers with no iodine overload (controls) and 1659 (35%) to mothers with iodine overload. Compared with the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 7 publications
1
44
2
Order By: Relevance
“…The results showed that the rate of recall was significantly increased among deliveries using povidone iodine and also among neonates who were breast-fed [13]. According to the announcement of the Isfahan CH screening project committee, maternity hospitals were advised not to use povidone iodine as far as possible during the course of delivery, but it cannot be ascertained that this recommendation has been accepted and implemented carefully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the rate of recall was significantly increased among deliveries using povidone iodine and also among neonates who were breast-fed [13]. According to the announcement of the Isfahan CH screening project committee, maternity hospitals were advised not to use povidone iodine as far as possible during the course of delivery, but it cannot be ascertained that this recommendation has been accepted and implemented carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Different surveys have been implemented to study recalls and factors affecting recall rate in CH screening programs [2,10,11,12,13,14,15]. The different recall rates in various screening programs are suggested to be due to several factors [1]: the use of T4 or TSH level or both for screening [2], differences in sample collecting methods and laboratories [3,] different established criteria for recalling that is related to cultural, regional, and social factors of a community.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive maternal iodine intake is one of the well-known causes of neonatal transient hypothyroidism or hyperthyrotopinemia [1,2,3,4,5,6]. Excessive maternal iodine intake may arise due to the consumption of iodine-rich foods, such as seaweed, and iodine-containing medicines.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of iodine incorporated after gargling using PVP-I cannot be neglected. Therefore, long-term use of PVP-I for gargling should be avoided in people with a high risk of developing thyroid dysfunction due to excessive intake of iodine, such as those with existing thyroid disease [1, 6, 11, 12], and in pregnant women [12, 13, 14] and breast-feeding mothers [15], because of possible effects on the thyroid function of their babies.…”
Section: Discussionmentioning
confidence: 99%